The Role and Therapeutic Potential of Macropinocytosis in Cancer - Qiu, Zejing; Liu, Wencheng; Zhu, Qianru; Ke, Kun; Zhu, Qicong; Jin, Weiwei; Yu, Shuxian; Yang, Zuyi; Li, Lin; Sun, Xiaochen; Ren, Shuyi; Liu, Yanfen; et al. (Frontiers in Pharmacology, 2022)
Macropinocytosis, a unique endocytosis pathway characterized by nonspecific internalization, plays a vital role in taking up extracellular substances and antigen presentation. Currently, it is well appreciated that macropinocytosis has a dual effect on cancer cells, which depends on cancer types and certain microenvironmental conditions. Macropinocytosis helps cancer cells to survive in a nutrition-deficient environment, resistant to anticancer drugs and promote invasion and metastasis. In contrast, overexpression of the RAS gene and drug treatment can lead to methuosis, a novel mode of cell death. Macropinocytosis is closely related to the tumor microenvironment (TME) to help the survival and proliferation of cancer cells. Understanding how cancer cells interact with the tumor microenvironment (TME) is critical for developing medicines that can halt tumor progression and metastasis. In addition, the research on anti-cancer therapy design for the effect of macropinocytosis has made substantial progress in recent years. Both inducing micropinocytosis and inhibiting micropinocytosis can be the ways against cancer cells. This article systematically reviews the general process of macropinocytosis, the specific functions of macropinocytosis in cancer cells, the connection of macropinocytosis with non-tumor cells in the TME, and its application in tumor therapy. It aims to understand the role and find the therapeutic potential of macropinocytosis in cancer to benefit cancer patients.